Tuning surface wettability of Al and its correlation with short and long term corrosion resistance in saline solutions - Khajavian, Ehsan; Attar, Mohammad Reza; Mohammadi-Zahrani, Ehsan; Liu, Wei; Davoodi, Ali; Hosseinpour, Saman (Surface & Coatings Technology, 2021)
In this work, we fabricated superhydrophilic aluminum alloy (AA 6063) with a hierarchical labyrinth-like structure using a facile and environmentally benign chemical etching method. The patterned samples were functionalized by stearic acid molecules to obtain superhydrophobic samples with water contact angle (CA) >160°, at optimum conditions. Although the superhydrophobic samples initially exhibited up to two orders of magnitude better corrosion resistance compared to as-received samples, their corrosion performance and CA gradually reduced upon prolonged exposure to 3.5 wt% NaCl solution. Hence, the initial high CA in superhydrophobic surface layers cannot be used as a measure of their long-term corrosion stability.